Enhancing Teaching Competency of Art Teachers in Public Elementary School :A Case Study of One County School in China - Deng, Na; Fernando, Maria Socorro C L (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
With the large-scale implementation of quality education, art education has received increasing attention from society and the government. The effectiveness of art education is closely related to the professional ability of art teachers. The research on the professional ability of primary school art teachers do not only promote the professional development of the teachers, but also foster the aesthetic ability and creativity of children. The purpose of this research is to understand the current situation of the professional competence of primary school art teachers in China's X area and to explore the impact of primary art teachers' soft skills in critical thinking, problem-solving, communication, teamwork, and information management skills on teaching competency. This study utilized quantitative research using a survey questionnaire on 121 primary school art teachers in the district. Multiple linear regression was used for data analysis. The results show that communication skills and problem-solving skills impact the teaching competency of primary and secondary school teachers in the study area. Teachers emphasized the importance of communication skills for classroom teaching, public speaking, and listening skills. Teachers adapted ways to solve problems properly and motivate students to learn, which could significantly boost teachers’ confidence and improve teachers’ competence. Based on the main findings of this study, a strategic plan was developed to enable these teachers to acquire more important teaching competencies. It can improve the teachers’ capability, which may help to contribute to the development of China’s education in the long run.